2021
DOI: 10.1111/tmi.13595
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of switch to paediatric second‐line antiretroviral therapy after first‐line failure in Cameroon

Abstract: Objective With scale‐up of antiretroviral therapy (ART) children, treatment failure and switch to subsequent ART regimens are common. Our objectives were to evaluate switching practices and identify factors associated among children and adolescents failing their first‐line ART. Methods A facility‐based survey study was conducted in a cohort of children living with HIV experiencing virological failure (VF) at the Essos Hospital Centre of Yaounde, Cameroon. Data were collected using a standard questionnaire, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The study finding also revealed that being an orphan child was significantly associated with second-line switch. The findings of a recent pediatric study conducted in Cameroon supported this association [33]. Children are dependent on their parents and require continual support due to their age and developmental stages.…”
Section: Plos Onementioning
confidence: 76%
“…The study finding also revealed that being an orphan child was significantly associated with second-line switch. The findings of a recent pediatric study conducted in Cameroon supported this association [33]. Children are dependent on their parents and require continual support due to their age and developmental stages.…”
Section: Plos Onementioning
confidence: 76%
“…Globally, numbers of children living with HIV (CLHIV) accessing first-line antiretroviral therapy (ART) have increased; coupled with increasing HIV viral load (VL) monitoring, numbers requiring second-line and subsequent ART following virological failure will also increase. 1–3 The majority of CLHIV live in Africa and until recently first-line non-nucleoside-reverse-transcriptase (NNRTI)-containing regimens were most frequently used. 3 For second-line ART following NNRTI failure, guidelines recommend an anchor drug from a new class (boosted protease inhibitor (bPI) or integrase inhibitor (INSTI)), combined with 2 nucleoside-reverse-transcriptase-inhibitors (NRTIs).…”
Section: Introductionmentioning
confidence: 99%